Robust implementation in rationalizable strategies in general mechanisms - KUNIMOTO, Takashi (Institutional Knowledge at Singapore Management University, 2024)
A social choice function (SCF) is robustly implementable in rationalizable strate-gies if every rationalizable strategy proﬁle on every type space results in outcomes consistent with it. First, we establish an equivalence between robust implementation in rationalizable strategies and “weak rationalizable implementation”. Second, using the equivalence result, we identify weak robust monotonicity as a necessary and al-most suﬃcient condition for robust implementation in rationalizable strategies. This exhibits a contrast with robust implementation in interim equilibria, i.e., every equilib-rium on every type space achieves outcomes consistent with the SCF. Bergemann and Morris (2011) show that strict robust monotonicity is a necessary and almost suﬃcient condition for robust implementation in interim equilibria. We argue that strict robust monotonicity is strictly stronger than weak robust monotonicity, which further implies that, within general mechanisms, robust implementation in rationalizable strategies is more permissive than robust implementation in interim equilibria. The gap between robust implementation in rationalizable strategies and that in interim equilibria stems from the strictly stronger nonemptiness requirement inherent in the latter concept.